Potential Strategies to Improve Antimicrobial Utilisation in Hospitals in Bangladesh Building on Experiences Across Developing Countries (Bangladesh Journal of Medical Science, 2021)
Abstract not availableBangladesh Journal of Medical Science Vol.20(3) 2021 p.469-477